Faktor Risiko Kerusakan Sel Beta Pankreas Melalui Deteksi Antibodi Gad (Glutamic Acid Decarboxylase) 65 pada Perempuan di Stikes Hang Tuah Surabaya - Rinarto, Nisha Dharmayanti (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Pancreatic beta cell damage is irreversible due to ongoing oxidative stress on the formation of ROS underlying pathophysiology of the phase-onset diabetes mellitus. Prevention of damage to pancreatic beta cells in diabetes mellitus onset phase through the detection of GAD 65 as an autoantigen imonogenik diabetes mellitus in human pancreas reacts with GADA can be done early. The purpose of this study analyzed the age, physical activity, cholesterol, body mass index, and waist circumference as a risk factor in the positive expression of GAD 65 women's groups in serum STIKES Hang Tuah Surabaya. This study was cross sectional study. Samples are some women in STIKES Hang Tuah Surabaya as much 40 respondents who meet the inclusion and exclusion criteria were selected through probability sampling techniques. The result of the relationship with the independent variable dependent variable using Chi Square showed that age (p = 0.395), physical activity (p = 0.572), BMI (p = 0.388), and waist circumference (p = 0.411) so it is not a risk factor for damage pancreatic beta cells. While cholesterol (p = 0.035) so it is a risk factor for pancreatic beta cell destruction. The conclusion of this study was in women aged 19-37 years with risk factors that can be used as a prediction of pancreatic beta cell destruction via antibody detection GAD 65 is high cholesterol.Keywords: Pancreatic Beta Cell Destruction, GAD 65, Women